P–065 Advanced paternal age does affect egg donation program outcomes?. (6th August 2021) - Miguens, M; Quinteir. Retamar, A M; Acosta, D; Veg. Balbuena, G; Carreras, E; Coscia, A; Papier, S
Abstract: Study question: Does increasing paternal age has a negative impact in fertilization (FR), blastulation (BR), clinical pregnancy (CPR) and miscarriage (MR) rates in an egg donation program? Summary answer: The increase paternal age in an egg donation program has not a negative impact in fertilization rate, blastulation rate, clinical pregnancy rates and miscarriage rates. What is known already: It is well documented that semen quality is affected with increasing paternal age but there is no evidence-based definition of what is advanced paternal age. There is controversial information about if the increasing paternal age affects in vitro fertilization results, and when this negative impact could begin. Study design, size, duration: This was a single center retrospective cohort study, involving 485 first single embryo transfer of an egg donation program, from January 2017 to December 2019. Participants/materials, setting, methods: All first embryo transfer of egg donation cycles performed at CEGyR, Buenos Aires, Argentina were included. Elevated sperm DNA fragmentation (TUNEL >20), sperm bank, and testicular biopsy cycles were excluded. Patients were divided according to male partner age: (1) <41, (2) 41–44, (3) 45–50 and (4) >50 years old. Group (1) was considered the control group. Statistical analyses were performed for FR and BR with ANOVA and CPR and MR with chi-squared tests. Main results and the role of chance: The number of patients in group (1) was 200, in (2) 130, in (3) 117 and in (4) 38. Male average age was 36, 8 in group (1), 42, 2 in (2) 47, 1 in (3) and 54, 2 in group (4). The FR in group (1) was 72, 60%, in group (2) was 73%, in (3) was 75% and 73% in (4). ANOVA results for FR: F = 0, 65 (p: 0, 58). The BR, defined as the relation between the total number of blastocysts over the number of fertilized oocytes in a cycle, was in group (1) 46, 35%, in group (2) was 45%, in group (3) 46%, and in group (4) 42%. ANOVA results for BR F = 0, 36 (p:0, 78). The CPR in group (1) was 42, 19%. Comparing with the other groups: group (2) was 37, 09% (chi-square statistic=0, 64 p:0, 43); group (3) 34, 58% (2, 32 p:0, 13); and group (4) was 32, 43% (1, 48 p:0, 22). The MR in group (1) was 12, 49%. Comparing with the other groups: group (2) was 18, 55% (chi-square statistic=2, 31 p:0, 12); group (3) 14, 94% (1, 01 p:0, 32); and group (4) was 15, 85% (0, 91 p:0, 33). For all results analyzed there were not a statistically difference between groups. Limitations, reasons for caution: The main limitation of this study was its retrospective design based on data from a single center which may be subject of bias. Wider implications of the findings: Further large prospective studies are required to make meaningful comparisons. Our findings give no support for a general recommendation. Trial registration number: Not applicable